2012
DOI: 10.1128/jcm.01946-12
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Extensively Drug-Resistant Tuberculosis Cases from Valle del Cauca, Colombia

Abstract: Extensively drug-resistant tuberculosis (XDR-TB), which is TB resistant to isoniazid and rifampin plus one fluoroquinolone and a second-line injectable drug, represents an obstacle for the treatment and control of TB. Previously, we reported four XDR-TB cases and a high proportion of the Beijing genotype among multidrug-resistant TB (MDR-TB) isolates in the state of Valle del Cauca, Colombia (3), where a MDR-TB hot spot had been identified (7). According to the information of the local TB program, to date 21 X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 7 publications
4
10
0
1
Order By: Relevance
“…Nevertheless, making a distinction between Beijing sublineages suggested a link between drug-resistance and certain genotypes. As already observed in recent studies from Colombia [37,38,39], an emerging SIT190 was well spread in Americas, particularly associated with MDR-TB and female patients. We observed that SIT190 was significantly more associated with MDR-TB than SIT1 (pvalue<0.0001).…”
Section: Drug-resistancesupporting
confidence: 54%
“…Nevertheless, making a distinction between Beijing sublineages suggested a link between drug-resistance and certain genotypes. As already observed in recent studies from Colombia [37,38,39], an emerging SIT190 was well spread in Americas, particularly associated with MDR-TB and female patients. We observed that SIT190 was significantly more associated with MDR-TB than SIT1 (pvalue<0.0001).…”
Section: Drug-resistancesupporting
confidence: 54%
“…The majority of the strains evaluated were isolated in the Valle del Cauca state, where an MDR-TB hot spot was detected previously (9), in addition to a high proportion of the Beijing genotype among MDR-TB cases (10), and where 10 out of 14 XDR-TB cases were detected (11). Information on the performance of these tests in Colombia is valuable, because the use of rapid molecular tests to detect resistance to antituberculosis drugs has become an important tool in the fight against MDR-TB and XDR-TB.…”
Section: Discussionmentioning
confidence: 99%
“…Perú and Colombia, the two countries that share a border with Ecuador, had communicated the presence of this lineage with a high prevalence in certain settings (16,17). This information led to the consideration that limitations in sample size could be responsible for the lack of detection of Beijing isolates in Ecuador.…”
Section: Discussionmentioning
confidence: 99%